Brucella infection and Toll-like receptors - Yu, Hui; Gu, Xinyi; Wang, Danfeng; Wang, Zhanli (Frontiers in Cellular and Infection Microbiology, 2024)
Brucella consists of gram-negative bacteria that have the ability to invade and replicate in professional and non-professional phagocytes, and its prolonged persistence in the host leads to brucellosis, a serious zoonosis. Toll-like receptors (TLRs) are the best-known sensors of microorganisms implicated in the regulation of innate and adaptive immunity. In particular, TLRs are transmembrane proteins with a typical structure of an extracellular leucine-rich repeat (LRR) region and an intracellular Toll/interleukin-1 receptor (TIR) domain. In this review, we discuss Brucella infection and the aspects of host immune responses induced by pathogens. Furthermore, we summarize the roles of TLRs in Brucella infection, with substantial emphasis on the molecular insights into its mechanisms of action.